The Information Component of Agricultural Research in Ghana (Journal of Science and Technology, 2016)
The place of agriculture in the overall national development of the country is underscored with a focus on the establishment of national centres for agricultural research. Problems of agriculture and food production in Sub-Saharan Africa, including Ghana, are highlighted and the need for strengthening local research into improved technology stressed. The present state of agricultural research in Ghana is outlined tracing the rather poor state of agricultural information services to foreign exchange constraint and inadequate allocation of local funds. It is concluded that information is the main input and output of every research endeavor and must be catered for in any viable and relevant agricultural research system, Recommendations include the appointment of an information professional on NARC; the inclusion of Agricultural Information Services and Systems in the Library School curriculum and the formation of an association for agricultural